2015
DOI: 10.1093/jnci/djv040
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Murine Breast Tumor Vascularity, Hypoxia, and Chemotherapeutic Response by Exercise

Abstract: Exercise has been shown to improve postischemia perfusion of normal tissues; we investigated whether these effects extend to solid tumors. Estrogen receptor–negative (ER-, 4T1) and ER+ (E0771) tumor cells were implanted orthotopically into syngeneic mice (BALB/c, N = 11–12 per group) randomly assigned to exercise or sedentary control. Tumor growth, perfusion, hypoxia, and components of the angiogenic and apoptotic cascades were assessed by MRI, immunohistochemistry, western blotting, and quantitative polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
237
3
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(278 citation statements)
references
References 30 publications
19
237
3
9
Order By: Relevance
“…Studies have shown that endurance training is associated with increased angiogenesis and vascularization in orthotropic mammary and prostate tumors from exercising mice and that such increased vascularization is correlated with enhanced blood perfusion and reduced tumor growth [72][73][74][75][76]. In addition to these long-term training studies in mice, McCullough et al have shown that perfusion of orthotropic prostate tumors increases immediately during treadmill running in tumor-bearing rats (as evidenced by in vivo injection of Hoechst-33342 stained tumor cells prior to animal culling) [74].…”
Section: Additional Exercise Effectsmentioning
confidence: 99%
“…Studies have shown that endurance training is associated with increased angiogenesis and vascularization in orthotropic mammary and prostate tumors from exercising mice and that such increased vascularization is correlated with enhanced blood perfusion and reduced tumor growth [72][73][74][75][76]. In addition to these long-term training studies in mice, McCullough et al have shown that perfusion of orthotropic prostate tumors increases immediately during treadmill running in tumor-bearing rats (as evidenced by in vivo injection of Hoechst-33342 stained tumor cells prior to animal culling) [74].…”
Section: Additional Exercise Effectsmentioning
confidence: 99%
“…Importantly the increase in tumor blood flow resulted in a significant reduction in tumor hypoxia (Figure 10). The ability to modulate tumor hypoxia by exploiting the systemic effects of exercise and the dysfunctional vasculature of solid tumors have recently been duplicated in rodent mammary tumor models grown in the mammary fat pads (Betof et al, 2015; Lee et al, 2015). …”
Section: The Tumor Microenvironment As a Double Edged Swordmentioning
confidence: 99%
“…Secondly, exercise has proven to mobilize and activate immune cells which are involved in the host-tumor defense, such as natural killer cells and cytotoxic T-cells [26,27]. Thirdly, it was speculated that exercise influences intratumoral angiogenesis [28]. Research of the past decade suggests, that some of the mentioned effects of PA are driven by exercise-induced epigenetic modifications [29,30].…”
Section: Physical Activity and Cancermentioning
confidence: 99%